2009
DOI: 10.1016/j.snb.2008.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Current-polarized ion-selective membranes: The influence of plasticizer and lipophilic background electrolyte on concentration profiles, resistance, and voltage transients

Abstract: Lipophilic background electrolytes consisting of a lipophilic cation and a lipophilic anion, such as tetradodecylammonium tetrakis(4-chlorophenyl) borate (ETH 500), or bis(triphenylphosphoranylidene) ammonium tetrakis[3,5bis(trifluoromethyl) phenyl] borate (BTPPATFPB) are incorporated into the membranes of ion-selective electrodes (ISEs) to improve the detection limit and selectivity of the electrodes and decrease the resistance of the sensing membrane. In this work, spectroelectrochemical microscopy (SpECM) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Diffusion coefficients have been calculated previously for free and complexed ETH5234 from chronoamperometric ( D L =2.3 × 10 −8 cm 2 /s) and potentiometric ion breakthrough experiments (DILnormalkn+=0.85×108cm2/s), respectively [3]. The TFPB − anion diffusion coefficient inferred from SpECM measurements is D R − = 1.1 × 10 −8 cm 2 /s [24]. By using these diffusion coefficients in combination with Eqs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diffusion coefficients have been calculated previously for free and complexed ETH5234 from chronoamperometric ( D L =2.3 × 10 −8 cm 2 /s) and potentiometric ion breakthrough experiments (DILnormalkn+=0.85×108cm2/s), respectively [3]. The TFPB − anion diffusion coefficient inferred from SpECM measurements is D R − = 1.1 × 10 −8 cm 2 /s [24]. By using these diffusion coefficients in combination with Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration profiles in neutral ionophore-based cation-selective membranes during an applied current step have been described previously. The membrane formulations for which the theory is derived consist of a plasticized polymeric matrix that incorporates the ionophore and a mobile cation exchanger (lipophilic anion) [7, 23, 24]. Eqs.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…0.5% Tetradodecylammonium tetrakis-(4-chlorophenyl)borate as lipophilic additives was added (Table 1). The results showed that the carbon paste electrode with ion-pair ratio of 5% has the best performance characteristics (slope, 28 28) The influence of plasticizer type on the performance characteristics of Panc sensors was investigated by using four plasticizers with different polarities (DBP, DOP, DOS, and TCP). The results reveal that DBP is the best of the plasticizers tested.…”
Section: Resultsmentioning
confidence: 99%
“…The equations for the ion-ionophore complex were derived with the assumption that ion-pair formation between the ion-ionophore complex and anion is negligible inside the membrane [21]. The equations are different for membranes without ion-ionophore complex migration, i.e., for membranes loaded with an excess of lipophilic electrolyte [3].…”
Section: Theorymentioning
confidence: 99%